A qualitative assessment of patient satisfaction with remote dermatology consultations utilized during the UK's first wave of the COVID‐19 pandemic in a single secondary care dermatology department. (27th July 2022) - Livesey, Amy; Plant, Alice; Simmonds, Roshni; Mitchell, Charles
Abstract : During the first wave of the SARS‐CoV‐2 coronavirus (COVID‐19) pandemic, many dermatology departments in the UK delivered remote consultations in order to minimize viral transmission. To assess patient perception of remote consultations delivered in a single dermatology department during this time, we retrospectively contacted patients via an electronic questionnaire and the responses are summarized. We anticipate that increased use of remote consultations will be a legacy of the pandemic, although healthcare professionals will have a responsibility for ensuring appropriate patient suitability.